2000
DOI: 10.1055/s-2000-9935
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Strangulation in a Neonatal Case: A Rare Complication of Permanent Epicardial Pacemaker Leads

Abstract: A newborn female underwent pacemaker implantation with epicardial pacing leads for the treatment of bradycardia caused by congenital atrioventricular block. At 10 months after pacemaker implantation, she was admitted with congestive heart failure. The epicardial leads were seen to encircle the heart, and myocardial ischemia was suggested. During cardiac catheterization she collapsed: emergency operation was performed, but she died on postoperative day 6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…A small study of 60 adults with an abandoned, noninfected epicardial leads found 20% were associated with a complication (lead migration 5, skin erosion 3, venous thrombosis 2, muscle stimulation 2) 10 . Another reported rare complication is cardiac strangulation by abandoned epicardial leads 11 . Intrapericardial diaphragmatic hernia is uncommon and usually related to prior trauma or iatrogenic causes 12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A small study of 60 adults with an abandoned, noninfected epicardial leads found 20% were associated with a complication (lead migration 5, skin erosion 3, venous thrombosis 2, muscle stimulation 2) 10 . Another reported rare complication is cardiac strangulation by abandoned epicardial leads 11 . Intrapericardial diaphragmatic hernia is uncommon and usually related to prior trauma or iatrogenic causes 12 .…”
Section: Discussionmentioning
confidence: 99%
“…10 Another reported rare complication is cardiac strangulation by abandoned epicardial leads. 11 Intrapericardial diaphragmatic hernia is uncommon and usually related to prior trauma or iatrogenic causes. 12 Two cases of intrapericardial diaphragmatic hernia related to epicardial pacing leads have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…One concern about placing an ICD coil directly into the pericardium is the potential for cardiac strangulation by the lead. There have been case reports of epicardial leads causing cardiac strangulation and congestive heart failure within several months of implantation 21 . There have also been reports of strangulation resulting from somatic growth 6 years after implantation 22 .…”
Section: Discussionmentioning
confidence: 99%
“…There have been case reports of epicardial leads causing cardiac strangulation and congestive heart failure within several months of implantation. 21 There have also been reports of strangulation resulting from somatic growth 6 years after implantation. 22 In an effort to minimize this potential complication, the ICD coil was sutured to the pericardium or epicardium to minimize the chance of lead migration.…”
Section: Innovative New Icd Lead Placementmentioning
confidence: 99%
“…Cases have more commonly been found postmortem or in patients presenting with symptoms of myocardial ischemia. [1][2][3][4] This case is unique in that the patient was completely asymptomatic at presentation. Continued awareness of the potential complications of pacemaker lead placement may help to detect further cases before the development of myocardial ischemia or infarction.…”
mentioning
confidence: 99%